ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI PURSED LIPS BREATHING UNTUK TINGKATKAN STATUS OKSIGENASI ANAK DENGAN ASMA DI RS BHAYANGKARA TK.1 R.SAID SUKANTO - Windu Syawalina Wahyuningsih, (2022)
Respiratory disease that often attacks children is asthma which is characterized by respiratory muscle weakness. As a result, the child's oxygenation status will deteriorate so that the child needs to do self-management to control asthma attacks with breathing exercises. Pursed lip breathing is breathing by pursed lips during expiration which can help flex and strengthen the respiratory muscles. The purpose of this study was to analyze nursing care by applying the pursed lip breathing in children with asthma. Respondents involved were 2 people including managed patients who were given pursed lip breathing and nursing care actions while in the treatment room, resumed patients were not given intervention. This intervention was carried out for three days with a frequency of once per day for 15 minutes. Measurement of oxygenation status includes pulse rate and oxygen saturation measured by cutaneous oximeter and respiratory rate by inspection technique. The results of the study on the third day showed an increase in oxygen saturation, a decrease in respiratory rate and an increase in pulse rate. Before it was done, RR : 26x/minute, HR: 109x/minute, SpO2: 95%. After that, the results showed that the patient's oxygenation status increased with RR: 21x/minute, HR: 119x/minute, SpO2: 99%.technique The pursed lips breathing is recommended for children with asthma in order to improve oxygenation status and as a complementary therapy to control, as well as reduce the recurrence of asthma.